Textual relationships and eclecticism on the Way to Heaven (Notes about the Mikelestorena’s book) - Salaberri Muñoa, Patxi (EGAN, 2021)
horretaz jarduteko. Gako-hitzak: XVIII. mendea, J.A. Mikelestorena, testu-erlazioak. ABSTRACT Author of a single book (Zerura nahi duenak har dezakeen bide erraza), the work of J. A. Mikelestorena has known several editions, all of them different and with remarkable characters. It is from them that this paper presents a set of observations about textual originality and/or dependence with respect to other works of the religious field corresponding to the eighteenth century. Keywords: